(3QSGdI aj JaSjQ bhdg JYGdi hdh CfeG aj GdCQV ef TLQI CbdGes - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; hGdJUdjI aEfc SCdJ Yf eYfi bhdg JYGdi (B: { (3hdh CfeG aj GdCQV ef TLQI CbdGe hGdHMQ jeOg ef HYOg SHYI CHMQ eG faOJ cdeGJ Gddg Ef Gddg YRjR Mcje (B} (3hYf bhdg JYGdi (B: {(3bd dh cGf GdHMQ eOGOG dcdeGJ QHj dfaO GdHMQ bHd Cf JfaO cdeGJ QHj (B}s
(3BNQgG (B:s
(3heKdg GHf (B( ) (3hRGO aEf bjd (B: (3Ef Jdc GdTQjYI dG JdRefG (B, (3aGdLhGH Cf cd eG CfRd Gddg YdjfG hEfeG CfRdg daGjOI ajg hefaYI dfG (B, (3hbGd ChdFc GdPjf gOi Gddg agOGge aBjI jhSa ebJOi HgG eYhd YdjgGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJaSjQ hYdhe GdbQBfs